KAHOOT! AS AN ALTERNATIVE ASSESSMENT IN ELT: TEACHER PERCEPTION - Aminullah Ismail; Munir Munir; Ryan Rayhana Sofyan (State University of Makassar, 2026)
This study aimed to investigate teachers' perceptions of the use of Kahoot as an alternative assessment in English language teaching and to explore the challenges encountered during its implementation. This study employed a descriptive qualitative research design involving two English teachers at CORE English School, Makassar. The data were collected through semi-structured interviews and analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings revealed that the teachers had positive perceptions of Kahoot as an alternative assessment, reflected in the cognitive, affective, and conative aspects. Cognitively, the teachers perceived Kahoot as an interactive learning medium and an assessment tool that supports formative assessment. Affectively, they expressed positive attitudes because Kahoot enhanced students' engagement, motivation, and enthusiasm during the learning process. Conatively, they consistently integrated Kahoot into their assessment practices while adapting its use to learning objectives and students' needs. The study also identified several challenges, including unstable internet connectivity, limited availability of digital devices, and limitations in assessing productive language skills. Overall, Kahoot was perceived as an effective alternative assessment that supports formative assessment, promotes students' engagement, and complements assessment practices in English language teaching.Keywords: alternative assessment, English language teaching, Kahoot!, teacher perception.